Bluefin tuna (Thunnus thynnus L.) farming on the Croatian coast of the Adriatic Sea: Present stage and future plans - Katavic I.; Franicevic V.; Ticina V. (Domestication of the bluefin tuna Thunnus thynnus thynnus, 2003)
In Croatia, during the last five years, bluefin tuna (BFT) farming reached around 2500 tons per year of harvested fish. The industry consists of 6 commercial companies using 9 lease sites. It was based on fishing BFT by purse seine and growing them in the 50 m diameter cages for a few months up to a couple of years. The BFT are fed small pelagic fish by hand, six days per week, twice per day. Farm mortality is about 3 per cent to 5 per cent per year, while stress-related mortality during the adaptation period is around 2 per cent. Daily feed consumption was in average around 5 per cent of biomass, within the temperature range from 18 degrees C to 24 degrees C. Some poorly planned and managed BFT operations had negatively impacted natural environment. The improvement of the environmental performances in BFT farming is of the highest importance for this industry in Croatia.
1. International Symposium on Domestication of the Bluefin Tuna Thunnus Thynnus Thynnus, 2002/02/03-08, Cartagena (Spain)